2023
DOI: 10.1007/s11845-023-03310-z
|View full text |Cite
|
Sign up to set email alerts
|

Ocular oncology service during the COVID-19 outbreak: uveal melanoma characteristics presenting in 2019 compared to 2020

Abstract: Aim We aim to evaluate the impact of the COVID-19 pandemic on ocular oncology in Ireland, comparing uveal melanoma trends in 2019 to 2020. Methods Patients included for analysis were those that presented to the ocular oncology service from January 2019 to December 2020 in the Royal Victoria Eye and Ear Hospital in Dublin, who underwent primary treatment for uveal melanoma—proton beam therapy, brachytherapy or enucleation. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 7 publications
5
11
0
Order By: Relevance
“…The number of T4 tumors increased from 8.78% in year 2018 to 26.26% in year 2021 and number of uveal melanomas localized anterior to the equator of the eye globe increased from 20.88% in year 2018 to 29.75% in year 2021, respectively. Our results were consistent with those from studies conducted in Spain and Ireland, where increased tumor size at diagnosis was found during the COVID-19 pandemic [17,19]. A study in the UK also found that more patients presented with more advanced cancers post lockdown [18].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The number of T4 tumors increased from 8.78% in year 2018 to 26.26% in year 2021 and number of uveal melanomas localized anterior to the equator of the eye globe increased from 20.88% in year 2018 to 29.75% in year 2021, respectively. Our results were consistent with those from studies conducted in Spain and Ireland, where increased tumor size at diagnosis was found during the COVID-19 pandemic [17,19]. A study in the UK also found that more patients presented with more advanced cancers post lockdown [18].…”
Section: Discussionsupporting
confidence: 92%
“…[18]. However, other studies did not confirmed this finding but those studies comprised of low number of patients [17,19,20].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations